Sulfonamide Inhibition Profile of the β-Carbonic Anhydrase from Malassezia restricta, An Opportunistic Pathogen Triggering Scalp Conditions - Sonia Del Prete; Andrea Angeli; Cynthia Ghobril; Julien Hitce; Cécile Clavaud; Xavier Marat; Claudiu T. Supuran; Clemente Capasso (Metabolites, 2020)
The critical CO2 hydration reaction to bicarbonate and protons is catalyzed by carbonic anhydrases (CAs, EC 4.2.1.1). Their physiological role is to assist the transport of the CO2 and HCO3− at the cellular level, which will not be ensured by the low velocity of the uncatalyzed reaction. CA inhibition may impair the growth of microorganisms. In the yeasts, Candida albicans and Malassezia globosa, the activity of the unique β-CA identified in their genomes was demonstrated to be essential for growth of the pathogen. Here, we decided to investigate the sulfonamide inhibition profile of the homologous β-CA (MreCA) identified in the genome of Malassezia restricta, an opportunistic pathogen triggering dandruff and seborrheic dermatitis. Among 40 investigated derivatives, the best MreCA sulfonamide inhibitors were dorzolamide, brinzolamide, indisulam, valdecoxib, sulthiam, and acetazolamide (KI < 1.0 μM). The MreCA inhibition profile was different from those of the homologous enzyme from Malassezia globosa (MgCA) and the human isoenzymes (hCA I and hCA II). These results might be useful to for designing CA inhibitor scaffolds that may selectively inhibit the dandruff-producing fungi.